Association of Tartrate-Resistant Acid Phosphatase-Expressed Macrophages and Metastatic Breast Cancer Progression. Issue 48 (December 2015) - Chen, Yu-Guang; Janckila, Anthony; Chao, Tsu-Yi; Yeh, Ren-Hua; Gao, Hong-Wei; Lee, Su-Huei; Yu, Jyh-Cherng; Liao, Guo-Shiou; Dai, Ming-Shen
Abstract : Abstract: Infiltrating neutrophils, lymphocytes, macrophages, and cytokines constitute a state of chronic inflammation within the tumor microenvironment. Tartrate-resistant acid phosphatase 5a (TRACP5a) protein, a novel product of activated macrophage, is postulated to be a biomarker for systemic inflammatory burden in states of chronic inflammation. We aimed to investigate the clinical significance of TRACP5a expression in tumor-infiltrating macrophages and serum TRACP5a in patients with metastatic breast cancer (BC). We retrospectively analyzed the clinical data from 34 BC patients with confirmed skeletal/visceral metastasis upon or during first-line palliative treatment. Patients were stratified into 3 groups based on the therapeutic responses and follow-up disease course. The association of TRACP5a protein with other inflammatory and cancer biomarkers was assessed among the clinically distinct group of patients. Higher TRACP5a protein was significantly correlated with earlier disease progression and survival ( P  = 0.0045) in comparison to other inflammatory markers, CRP or IL-6. Patients with higher serum TRACP5a level and shorter survival and treatment refractoriness also had more TRACP+ tumor-infiltrating macrophages. Our data support a hypothesis that serum TRACP5a protein can potentially be a predictive and prognostic marker to evaluate disease progression and therapeutic response in BC patients with bone/visceral metastasis. The associations between overall survival and TRACP expression by macrophages require further prospective investigation.